Methods of comprehensive statistical analysis of agglomeration atmospheric air pollution - Loyeva, Inesa; Bazar, Salem Rabeea; Burhaz, Oleksii; Vladymyrova, Olena (Видавництво Львівської політехніки, 2021)
The article presents an algorithm of a complicated statistical analysis of atmospheric air pollution over certain urban territories, based on methods of multivariate statistical analysis and a statistical decisions theory. Statistical analysis of the concentrations obtained from the observation posts network provides the data on the atmospheric air pollution background characteristics. This analysis enables us to find the spatial correlations between the concentrations of the ingredient under various synoptic conditions. The proposed set of statistical methods is advisable to be applied in the development of a state monitoring program for atmospheric air protection over specific zones or territories (urban agglomeration) as part of the implementation of a new management procedure for state monitoring of atmospheric air protection in Ukraine.
Keywords: air pollution; statistical methods; level of pollution assessment; monitoring